Secondary Succession of Vegetation in the Former Coal Mine Area PT. Bukit Asam Tbk - Yuanita Windusari; Umar Harun; Supomo Asnawi, Ariyono Suyono (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
Open-pit mining activities cause environmental degradation such as decreased soil fertility and degradation of plantation. After mining activities is completed, land improvements will be carried out through post-mining reclamation. Low pH conditions, high metal concentrations and low organic matter are the main problems in post-mining activities reclamation land. Reclamation activities carried out by PT. Bukit Asam, Tbk runs continuously from time to time. Mining land that is no longer used for mining activities must immediately carry out land reclamation activities to preserve the environment and maintain ecosystem stability in coal mining areas. The reclamation efforts that have been carried out require vegetation analysis to determine the vegetation growing on the reclaimed land of various ages. This research aims to analyze vegetation using the transect method in reclamation areas aged 1 year, 3 years, 5 years, and natural land as a control. The research results show that all reclaimed land is ultisol soil which is acidic (pH 3.52 – 4.50), and the older the reclaimed land can increase the C-Organic, C-Total and C/N of the soil. The condition of land that is 5 years old also has lower soil temperatures and greater humidity than land that is younger. The Importance Value Index (INP) of seedlings, saplings, poles and trees on reclaimed land at 1 year old is smaller than at 5 years old. The common vegetation found on all reclaimed land of different ages is seedlings (Mimosa pudica), saplings (Malaleuca cajuputi), poles and trees (Malaleuca cajuputi, Acacia mangium).